Trends and equity in the use of health services in Spain and Germany around austerity in Europe - Moreno, Almudena (Int J Equity Health, 2021)
BACKGROUND: Following the 2008 economic crisis many countries implemented austerity policies, including reducing public spending on health services. This paper evaluates the trends and equity in the use of health services during and after that period in Spain – a country with austerity policies – and in Germany – a country without restriction on healthcare spending. METHODS: Data from several National Surveys in Spain and several waves of the Socio-Economic Panel in Germany, carried out between 2009 and 2017, were used. The dependent variables were number of doctor’s consultations and whether or not a hospital admission occurred. The measure of socioeconomic position was education. In each year, the estimates were made for people with and without pre-existing health problems. First, the average number of doctor’s consultations and the percentage of respondents who had had been hospitalized were calculated. Second, the relationship between education and use of those health services was estimated by calculating the difference in consultations using covariance analysis – in the case of number of consultations – and by calculating the percentage ratio using binomial regression – in the case of hospitalization. RESULTS: The annual mean number of consultations went down in both countries. In Spain the average was 14.2 in 2009 and 10.4 in 2017 for patients with chronic conditions; 16.6 and 13.5 for those with a mental illness; and 6.4 and 5.9 for those without a defined illness. In Germany, the averages were 13.8 (2009) and 12.9 (2017) for the chronic group; 21.1 and 17.0 for mental illness; and 8.7 and 7.5 with no defined illness. The hospitalization frequency also decreased in both countries. The majority of the analyses presented no significant differences in relation to education. CONCLUSION: In both Spain and Germany, service use decreased between 2009 and 2017. In the first few years, this reduction coincided with a period of austerity in Spain. In general, we did not find socioeconomic differences in health service use.